Effects of Low Impact Aerobic Exercise on Increasing Lung Function Capacity in Adolescent (Universitas Pendidikan Indonesia, 2025)
Lung function capacity is the ability of the lungs to hold air when breathing. Lung function capacity plays an important role in a person physical fitness. Therefore, respiratory fitness training is determined by lung function in supporting daily physical activities. The purpose of this study was to examine the effect of low-impact aerobic exercise, by calculating the VO2max value, on lung function capacity in adolescents (male and female aged 18 to 21 years), totaling 134 respondents. The research method used pre-experimental with one group pre-test and post-test design. This study used a spirometry measuring instrument to calculate the VO2max value. Data analysis showed an increase of 14.3%. The result found that the lung function capacity of adolescents before being given exercise was in the medium and low categories. Meanwhile, after being given low-impact aerobic exercise for 12 weeks (36 treatments), there was a significant increase of VO2max in adolescents. The results of this study prove that low-impact aerobic exercise can significantly increase lung function capacity showed by the increase of VO2max in adolescents. This study provides knowledge with relevant novelty on healthy lifestyle patterns in adolescents. It is recommended that adolescents should change their lifestyle by doing aerobic physical activities routinely and structured for better health.